Design of CMOS‐MEMS broadband infrared emitter arrays integrated with metamaterial absorbers based on CMOS back‐end‐of‐line. (1st October 2016) - Cheng, Zhengxi; Toshiyoshi, Hiroshi
Abstract : A new design of complementary metal–oxide–semiconductor microelectromechanical systems (CMOS‐MEMS) broadband infrared (IR) emitter arrays with integrated metamaterial absorbers (MAs) developed by the CMOS back‐end‐of‐line is presented. The IR emitter array is a promising broadband thermal radiation source for integrated gas sensors. Novel IR emitter arrays are designed using the Central Semiconductor Manufacturing Corporation 0.5 μm 2‐poly‐3‐metal CMOS process. To improve the low emissivity that is commonly seen in CMOS‐MEMS type IR emitters due to the inherited low emissivity of SiO2 and SiN in CMOS process, we newly adopted tri‐layer metal–insulator–metal (MIM) and four‐layer insulator–MIM (IMIM) MA by using the CMOS back‐end metal layers and inter‐layer dielectrics, thereby to excite multi‐mode surface plasmon polariton resonances. The emitter integrated with IMIM MA can be electrically modulated up to 344 Hz, as theoretically predicated from thermal properties of the emitters and the radiation properties calculated based on Planck's radiation law. Simulated emissivity spectra through FEM show that the multi‐mode resonances in CMOS MIM and IMIM MAs enhance emissivity and broaden the waveband effectively.